The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd005340.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal chemotherapy for the initial management of primary epithelial ovarian cancer

Abstract: Background-Ovarian cancer tends to be chemosensitive and confine itself to the surface of the peritoneal cavity for much of its natural history. These features have made it an obvious target for intraperitoneal (IP) chemotherapy. Chemotherapy for ovarian cancer is usually given as an intravenous (IV) infusion repeatedly over five to eight cycles. Intraperitoneal chemotherapy is given by infusion of the chemotherapeutic agent directly into the peritoneal cavity. There are biological reasons why this might incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 21 publications
0
116
0
8
Order By: Relevance
“…10 Despite this proven advantage, the adoption of IP chemotherapy has been slow in North American oncologic centers. A recent survey of the members of the Society of Gynecologic Oncologist and the American Society of Clinical Oncology reported that the top reasons given by those not using IP chemotherapy were concerns regarding excessive toxicity (63%) and not having the facilities to administer an IP infusion (16%).…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite this proven advantage, the adoption of IP chemotherapy has been slow in North American oncologic centers. A recent survey of the members of the Society of Gynecologic Oncologist and the American Society of Clinical Oncology reported that the top reasons given by those not using IP chemotherapy were concerns regarding excessive toxicity (63%) and not having the facilities to administer an IP infusion (16%).…”
Section: Discussionmentioning
confidence: 99%
“…[18] GOG-172 was the third of three, large randomized studies [18,28,48] reporting a benefit for intraperitoneal chemotherapy. A Cochrane Systematic Review of all randomized trials of intraperitoneal chemotherapy in ovarian cancer involving 1819 patients also revealed an overall benefit of intraperitoneal chemotherapy [49].…”
Section: Front-linementioning
confidence: 99%
“…The Cochrane meta-analysis of these eight randomized trials enrolling 1819 patients showed that women who received an IP component of chemotherapy experienced a better progression-free survival (HR: 0.79, 95% CI: 0.69-0.90) and a better overall survival (HR: 0.79, 95% CI: 0.70-0.90) (73) . There was greater serious toxicity as gastrointestinal effects, pain, and fever but less ototoxicity with the IP treatment.…”
Section: Ip Chemotherapy As First-line Treatment In Patients With Minmentioning
confidence: 99%